Hakam dan Mediasi Dalam Perkara Syiqāq di Mahkamah Syar’iyah Bireuen Propinsi Aceh - Pagar Pagar; Zainul Fuad; Muhammad Muhammad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
The purpose of this study is to determine the role of the judge, to know the mediation process, to find out the obstacles and mediation solutions to the settlement of syiqāq cases in reducing the divorce rate at the Bireuen Syar'iyah Court. This research includes field research (fild research) with the type of qualitative research. Which focuses on the function of hakam and mediation in the Syiqaq Case which this research was conducted at the Bireun Syari'ah Court, Aceh. Data collection techniques used are interviews, observation and documentation. The primary sources in this research are the judges who are under the auspices of the Bireuen Syar'iyah Court, the community is directly involved in the Syiqaq case during the study. While the secondary sources are books, regulations and documents as well as laws related to this research and data in the form of documentation of the Syiqaq case at the Syar'iyah Court of Bireuen Regency. Data analysis techniques In this study using data analysis that is relevant to the data in this study, namely content analysis in order to be able to answer the problems that are the object of study in this study